Abiotic Bromination of Soil Organic Matter - Leri, Alessandra C; Ravel, Bruce (Environmental science & technology, 2015)
Biogeochemical transformations of plant-derived soil organic matter (SOM) involve complex abiotic and microbially mediated reactions. One such reaction is halogenation, which occurs naturally in the soil environment and has been associated with enzymatic activity of decomposer organisms. Building on a recent finding that naturally produced organobromine is ubiquitous in SOM, we hypothesized that inorganic bromide could be subject to abiotic oxidations resulting in bromination of SOM. Through lab-based degradation treatments of plant material and soil humus, we have shown that abiotic bromination of particulate organic matter occurs in the presence of a range of inorganic oxidants, including hydrogen peroxide and assorted forms of ferric iron, producing both aliphatic and aromatic forms of organobromine. Bromination of oak and pine litter is limited primarily by bromide concentration. Fresh plant material is more susceptible to bromination than decayed litter and soil humus, due to a labile pool of mainly aliphatic compounds that break down during early stages of SOM formation. As the first evidence of abiotic bromination of particulate SOM, this study identifies a mechanistic source of the natural organobromine in humic substances and the soil organic horizon. Formation of organobromine through oxidative treatments of plant material also provides insights into the relative stability of aromatic and aliphatic components of SOM.